Family Factors Associated With Immunization Uptake in Children Aged Between 12-59 months: A Household Survey in Kakamega Central District, Western Kenya - Luke, Joram Sunguti (Auckland University of Technology, 2014)
Immunization is regarded as one of the most important achievements of public health. Immunization coverage in children in Kenya is about 88%. Regional disparities however exist and these are mediated by provider, system and client related factors. The aim of this study was to assess complete immunization coverage and to identify family factors associated with immunization in children aged between 12 and 59 months in Kakamega Central, Western Kenya. A cross sectional study was conducted in 13 sub-locations between June and July, 2013. Stratified sampling was conducted followed by simple random sampling to identify households to be visited within each stratum. Data on 577 children were collected from their respective care givers by trained research assistants. Information collected included immunization status of the child, sociodemographic characteristics of the caregivers and their partners and the household’s socioeconomic status. Factors affecting immunization uptake were assessed through bivariable and multivariable logistic regression methods. The proportion of completely immunized children was 81.1% (95% CI 76.9%-85.3%). The immunization coverage rates for BCG, OPV3, DPT3 and measles were 99.4%, 85.3%, 96.0% and 92.4% respectively. At bivariable levels, the factors associated with immunization included caregiver’s age, education level of the caregiver and partner, the child’s birth order, maternal attendance of antenatal clinics, place of delivery of the child and socioeconomic status of the household. At multivariable levels, greater immunization uptake was predicted by high school level of the caregiver and partner, attendance of ANC clinics and delivery within a health facility. Immunization uptake in Kakamega central is still low compared to neighbouring regions. Various family sociodemographic characteristics are associated with immunization uptake. Further inquiry is required into this area to fully comprehend the inextricable linkage between factors affecting immunization.
Keywords: Vaccine; Vaccination; Immunized; Immunization; Determinants; Household survey